The Factors Affecting Decision to Use Currency Exchange Service with the Service Units of the Commercial Banks in Luang Prabang Capital - INSOMPHORN , Thanousin; SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone; SENGDARA, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this study is to study the factors affecting the decision to use currency exchange service unit of the commercial banks by using the econometric model. In this study, 246 questionnaires were used to collect information from customers who chose to use currency exchange service units of the commercial banks in Luang Prabang Municipality. The results of the multiple regression found that the personal factors there are only the level of education and income that affect the decision to use the exchange service unit of the commercial banks with a statistical significance level of 0.01, while the behavioral factor does not have an affects to the decision with a statistical significance level of 0.05. As for the marketing mix factors, only the distribution channel factor is not statistically significant. The product factor and the promotion factor affect to the decision level with a statistical significance level of 0.01 while the price factor results at a statistical significance level of 0.05. With the promotion factor influencing the decision to use exchange service units the most, followed by the product factor and the customer’s income with a significance level of 0.01. For the price factor, it has an effect on the level of decision to use exchange service unit of the commercial banks at the statistical significance level of 0.05 and the least effect is the level of education has a positive relationships with the level of decision to use the exchange service unit of the commercial banks at the level of statistical significance of 0.01.